Plan approval process / Nurulain Abd Ghani - Abd Ghani, Nurulain (Universiti Teknologi MARA UiTM,Perak, 2022)
The approval of a building plan entailed following regulations, laws, and standards in order to assure a methodical and orderly development. Since the 1980s, Malaysia's construction industry has grown, necessitating greater statutory regulations in getting approvals from the required authorities to commence and construct a facility, as well as to occupy and utilise the completed facility. It is critical to comprehend the building plan process in order to determine if the construction complies with building laws. This report was conducted for the house/building plan submission drawing. The objective of this report is to investigate the method of building plan approval and to determine the problems occurred and solutions taken to solve the problems. The first process to build a house is to submit the submission drawing to the authority such as District Office of Batu Pahat. As the consequence of that, the building construction flow can be smooth and efficient due to the less mistake done.